Trace Si-induced interfacial anchoring stabilizes Cu–CeO2 active sites for durable high-temperature reverse water–gas shift reaction - Linyu Zhang; Lulu Zhou; Liang Yuan; Haohao Feng; Jingfeng Han; Yongdong Chen (Chemical Engineering Journal, 2026)

Geomorphic conditions and anthropogenic irrigation as drivers of CO2 and CH4 emissions in Heihe River - Zhiheng Du; Wenhan Hu; Hao Cui; Lei Wang; Jingfeng Liu; Fangping Yan; Rinat Manasypov; Changlian Tao; Renjun Wang; Jing Luo; Chuntan Han; Xiqiang Wang (Global and Planetary Change, 2026)

A coupled rockfall-bridge damage assessment method integrating trajectory simulation and intrusion detection - Jingfeng Zhang; Jie Ma; Jizhuang Guo; Jiaxin Luo; Han Bao; Huaimao Yang (Engineering Structures, 2026)

In Vitro Antibacterial Activity of Glutathione Against Aeromonas veronii and Its In Vivo Effects on Intestinal Microbiota in Koi Carp ( Cyprinus carpio Var. koi ) - Haoyue Zhang; Jingfeng Sun; Zhuoran Han; Anli Wang (New Zealand Journal of Marine and Freshwater Research, 2026)
Aeromonas veronii is a pathogenic bacterium that threatens freshwater fish, including koi carp. Antibiotics used to control bacterial infections can disrupt the intestinal microbiota and promote antibiotic resistance. This study aimed to evaluate the in vitro antimicrobial activity of glutathione (GSH) against A. veronii and its impact on the intestinal microbiota of koi carp. To this end, we examined bacterial growth, biofilm formation, and motility of A. veronii . We further analyzed the intestinal microbiota composition by 16S rRNA high‐throughput sequencing and assessed disease resistance in koi carp after 7 days of dietary GSH supplementation. The results showed that GSH inhibited A. veronii growth, biofilm formation, and motility, with stronger effects at higher doses. GSH supplementation also significantly altered the intestinal microbiota, reducing potential pathogenic bacteria like Aeromonas and promoting beneficial ones. Moreover, GSH enhanced disease resistance, with treated fish showing lower cumulative mortality compared to controls. However, the GSH doses of 720 mg/kg caused hepatic burden, emphasizing the need for careful dose optimization. These findings highlight the significance of GSH in modulating the intestinal microbiota of fish, a process that may contribute to enhanced disease resistance, and emphasize the importance of optimizing its dosage for safe application in aquaculture.

Glutathione restores florfenicol-induced intestinal microecological imbalance in koi carp (Cyprinus carpio var. koi) - Zhuoran Han; Han Yang; Anli Wang; Guowei Han; Jingfeng Sun (Aquaculture, 2026)

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Electrochemically assisted activation of peroxymonosulfate by Cu-Co bimetallic carbon nitride for enhanced deoxynivalenol degradation - Bingjie Wang; Xi Zhang; Zhixia Wu; Chenyu Li; Jingfeng Wang; Xu Han (Journal of Environmental Chemical Engineering, 2025)

Machine learning enhanced bridge vulnerability quantification under rockfall hazards - Jingfeng Zhang; Yifan Jing; Jie Ma; Jiaxin Luo; Han Bao; Shizhi Chen (Engineering Geology, 2025)

Identification of carbon dioxide and methane emission characteristic across Heihe River, China - Wenhan Hu; Zhiheng Du; Lei Wang; Fangping Yan; Chuntan Han; Xiqiang Wang; Changlian Tao; Jingfeng Liu (Science of The Total Environment, 2025)

Relic DNA obscures bacterial diversity and interactions in ballast tank sediment - Zhaozhao Xue; Haoze He; Yangchun Han; Wen Tian; Shengjie Li; Jingfeng Guo; Pei Yu; Lina Qiao; Wei Zhang (Environmental Research, 2025)

Environmental RNA metabarcoding for ballast water microbial diversity: Minimizing false positives - Zhaozhao Xue; Wen Tian; Yangchun Han; Shengjie Li; Jingfeng Guo; Haoze He; Pei Yu; Wei Zhang (Science of The Total Environment, 2024)

Doppler Compensation Techniques for M-Ary Sequence Spread Spectrum Signals Based on Correlation Cost Factors in Mobile Underwater Acoustic Communication - Yubo Han; Shuping Han; Heng Zhao; Yaohui Hu; Jingfeng Xu; Gang Yang (Journal of Marine Science and Engineering, 2024)
Unlike terrestrial radio, the speed of sound in the ocean is relatively slow, which results in mobile underwater M-ary spread spectrum communication typically exhibiting significant and variable multipath effects along with strong Doppler effects, leading to rapid carrier phase shifts in the received signal that severely impact decoding accuracy. This study aims to address the issue of rapid carrier phase shifts caused by significant time-varying Doppler shifts during mobile underwater M-SS communication. This paper innovatively proposes a method for updating matched filters based on correlation cost factors. By calculating the correlation cost factors for each received symbol, the method guides the direction of Doppler estimation and updates the matched filters. After identifying the optimal match, the received symbols are shifted, correlated, and decoded. Simulation and sea trial results indicate that this method demonstrates higher computational efficiency and improved decoding accuracy compared to traditional Doppler estimation matched filters under low signal-to-noise ratio conditions, and exhibits greater robustness under complex motion conditions.

Ascorbic acid alleviates the autolysis of the sea cucumber Apostichopus japonicus via the activation of antioxidant enzymes to remove reactive oxygen species during live storage - Han Cai; Jun Zhao; Lu Wang; Yanjie Wang; Jie Zheng; Shuang Song; Jingfeng Yang (Aquaculture International, 2024)

A Deep Learning Approach for Forecasting Thunderstorm Gusts in the Beijing-Tianjin-Hebei Region - Yunqing Liu; Lu Yang; Mingxuan Chen; Linye Song; Lei Han; Jingfeng Xu (Advances in Atmospheric Sciences, 2024)

Transcriptomic and proteomic insights into the immune response of the intestine to Aeromonas veronii infection in koi carp (Cyprinus carpio var. koi) - Guowei Han; Zhuoran Han; Boyun Jiang; Yang Lu; Jingfeng Sun (Aquaculture, 2024)

Identification and functional characterization of annexin A2 in half-smooth tongue sole (Cynoglossus semilaevis) - Guowei Han; Yufeng Su; Qing Mao; Zhuoran Han; Jingfeng Sun (Fish & Shellfish Immunology, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Contrasting responses of relationship between solar-induced fluorescence and gross primary production to drought across aridity gradients - Ruonan Qiu; Ge Han; Xing Li; Jingfeng Xiao; Jiangong Liu; Songhan Wang; Siwei Li; Wei Gong (Remote Sensing of Environment, 2024)

Effects of a multistrain probiotic on the growth, immune function and intestinal microbiota of the tongue sole Cynoglossus semilaevis - Zhongjie Zan; Kun Chen; Haoyi Wang; Zhuoran Han; Jingfeng Sun (Aquaculture, 2023)

Exploring the bacterial diversity and composition with special emphasis on pathogens in ship ballast water and sediments using full-length 16S rRNA gene sequencing - Tingxuan An; Xiaolan Lu; Yangchun Han; Chong Guo; Jingfeng Guo; Guorong Zhu; Wen Tian; Baoyi Lv (Marine Pollution Bulletin, 2023)

Transcriptomic analysis of the hepatopancreas of white shrimp Penaeus vannamei following experimental infection with the Vibrio parahaemolyticus TJA114 - Xue Zhang; Zhuoran Han; Feng Chen; Xueliang Sun; Jingfeng Sun (Aquaculture, 2023)

Dysfunction of the intestinal physical barrier in the intestinal inflammation of tongue sole, Cynoglossus semilaevis, induced by Shewanella algae infection - Zhuoran Han; Lunhua Ge; Siyi Wen; Jingfeng Sun (Fish & Shellfish Immunology, 2023)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Diversity and structure of bacterial communities in Fildes Peninsula, King George Island - Jingfeng Fan; Lili Li; Junli Han; Hongxia Ming; Jiangyu Li; Guangshui Na; Jiaying Chen (Polar Biology, 2013)

Molecular characterization of influenza B viruses isolated in east-central China in 2009–2010 - Na Zhu; Peng Li; Jingfeng Yu; Yongdong Li; Jiuru Zhao; Han Xia; Shuang Tang; Zhong Zhang; Zheng Kou; Shiyu Yin; Zhaojun Fan; Tianxian Li (Virus Genes, 2013)